Short Sleep Duration Is Positively Associated With Traditional and Non‐Traditional Markers of Adiposity and Cardiometabolic Risk in Individuals at Secondary Healthcare: A Cross‐Sectional Study - Nathallia Maria Cotta e Oliveira; Mariana De Santis Filgueiras; Gilmara Alves Zanirate; Flávia Galvão Cândido; Sarah Aparecida Vieira Ribeiro; Helen Hermana Miranda Hermsdorff (The FASEB Journal, 2026)
ABSTRACT This study aimed to investigate the associations between short and long sleep duration and traditional and non‐traditional markers of adiposity and cardiometabolic risk. This is a cross‐sectional study that enrolled secondary data of 937 men and women ≥ 18 years assisted at Secondary Healthcare. Traditional markers of adiposity and cardiometabolic risk were waist circumference, body mass index, triglycerides, glucose, glycated hemoglobin, systolic (SBP) and diastolic (DBP) blood pressure, while the non‐traditional were deep‐abdominal‐adipose‐tissue index, visceral adiposity index (VAI), lipid accumulation product index, Castelli risk index 1 and 2, TG/HDL‐c ratio, atherogenic index of plasma, and triglyceride‐glucose index (TyG index). Self‐reported habitual sleep durations were classified as short, recommended, or long according to the National Sleep Foundation. The prevalence ratios (PRs) were estimated by Poisson regression models, adjusted for potential confounders ( α = 0.05). The prevalence of short and long sleep was 9.8% (5.9 ± 0.7 h/night) and 36.7% (10.5 ± 1.3 h/night), respectively. Short sleep was positively associated with abdominal obesity (PR: 1.15; 95% CI: 1.01–1.23), overweight (PR: 1.11; 95% CI: 1.00–1.24), high VAI (PR: 1.36; 95% CI: 1.04–1.77), high TyG index (PR: 1.44; 95% CI: 1.09–1.89), and high DBP (PR: 1.35; 95% CI: 1.07–1.72), regardless of confounders. No association between long sleep and cardiometabolic risk was found. In conclusion, individuals at high cardiovascular risk with short sleep duration are more likely to have adiposity‐related risk, insulin resistance, and diastolic blood pressure imbalance.